HISTORY OF THE DEVELOPMENT OF TECHNICAL DEVICES AND THE DEVELOPMENT OF INFORMATION TRANSMISSION (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
this article discusses technical security tools, their types and applications, forms of information transmission, wired and wireless views of the information transmission system and their use.